Comprehensive study of antibacterial activities of medicinal plants and essential oils against Staphylococcus aureus - Tawhid, Tasfia (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2021.